2013
DOI: 10.3109/1040841x.2013.804032
|View full text |Cite
|
Sign up to set email alerts
|

Autotransporter-based cell surface display in Gram-negative bacteria

Abstract: Cell surface display of proteins can be used for several biotechnological applications such as the screening of protein libraries, whole cell biocatalysis and live vaccine development. Amongst all secretion systems and surface appendages of Gram-negative bacteria, the autotransporter secretion pathway holds great potential for surface display because of its modular structure and apparent simplicity. Autotransporters are polypeptides made up of an N-terminal signal peptide, a secreted or surface-displayed passe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 145 publications
0
57
0
Order By: Relevance
“…Autotransporter proteins are typically VFs in P. multocida (Nicolay et al, 2015). The gene icsA (OG1421) encoding an autotransporter related to the Type V secretion system, was undergoing significantly positive selection (FDR = 0.002) (Table S7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autotransporter proteins are typically VFs in P. multocida (Nicolay et al, 2015). The gene icsA (OG1421) encoding an autotransporter related to the Type V secretion system, was undergoing significantly positive selection (FDR = 0.002) (Table S7).…”
Section: Discussionmentioning
confidence: 99%
“…It was worth noting that intragenic homologous recombination also occurred on icsA (2,556 nt), with one breakpoint at position 331 (Table S6). The outer membrane protein IcsA of P. multocida harbors a β-barrel domain (PF03797) at the C-terminal followed by an α-helical linker essential for outer membrane translocation of the passenger domain pertactin (PF03212) with characteristic β-helix (Nicolay et al, 2015). Structural mapping of seven positively selected sites on IcsA showed that the majority of sites (i.e., residues 159, 220, 315, 481, and 690) were located at the loops connecting the β-strands (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of the above systems led us to explore alternative E. coli display systems for the selection of Nbs (and perhaps other Ab fragments). An important clue came from the study of a large family of proteins secreted by Gram‐negative bacteria called autotransporters (ATs; Henderson et al ., ; Nicolay et al ., ). Classical ATs contain within their sequence a C‐terminal β‐barrel, comprising of 12 antiparallel β‐strands and an internal α‐helix (Oomen et al ., ; van den Berg, ; Gawarzewski et al ., ), which acts as a ‘helper’ domain assisting the translocation of the N‐terminal portion of the polypeptide across the OM.…”
Section: E Coli Displaymentioning
confidence: 99%
“…This research has led to the use of AT proteins as vaccine candidates, whereby pertactin from Bordetella pertussis or NadA from Neisseria meningitidis are constituents of human vaccines . Furthermore, the seemingly simple AT secretion system has also attracted attention for biotechnological applications as a carrier of heterologous proteins to the bacterial cell surface . This review describes the AIDA‐I type ATs in E. coli strains, which are representative of the great diversity of AT adhesins in Gram‐negative bacteria.…”
Section: Introductionmentioning
confidence: 99%